The Role of Information Technology and Employee Ability on the Effectiveness of Accounting Information Systems - Utomo, Langgeng Prayitno (STIE PGRI Dewantara Jombang, 2019)
The effectiveness of accounting information systems is a success achieved by accounting information systems in producing information in a timely, accurate, and reliable manner. This study aims to determine the role of information technology and employee knowledge of the accounting department on the effectiveness of accounting information systems. This research was an associative - quantitative type with a survey approach. The sample in this study were all managers and employees of the financial division of the Republic of Indonesia Employee Cooperative in Jombang Regency (saturated sample). The data used were primary data obtained through questionnaires. The data analysis technique used multiple linear regression analysis. The results of this study indicated that the sophistication of information technology and the knowledge of employees of the accounting department had a positive and significant effect on the effectiveness of the accounting information system.